2016
DOI: 10.1002/ece3.2601
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating citizen science data for forecasting species responses to national forest management

Abstract: The extensive spatial and temporal coverage of many citizen science datasets (CSD) makes them appealing for use in species distribution modeling and forecasting. However, a frequent limitation is the inability to validate results. Here, we aim to assess the reliability of CSD for forecasting species occurrence in response to national forest management projections (representing 160,366 km2) by comparison against forecasts from a model based on systematically collected colonization–extinction data. We fitted spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 51 publications
(77 reference statements)
4
48
0
Order By: Relevance
“…We used the estimates on living tree volumes and forest age to calculate different connectivity measures as in Mair et al. (, see Appendix b). We tested three different dispersal parameters representing mean dispersal distances of 1 km, 5 km and 10 km and included the connectivity variable which best explained the occurrence of a focal species.…”
Section: Methodsmentioning
confidence: 99%
“…We used the estimates on living tree volumes and forest age to calculate different connectivity measures as in Mair et al. (, see Appendix b). We tested three different dispersal parameters representing mean dispersal distances of 1 km, 5 km and 10 km and included the connectivity variable which best explained the occurrence of a focal species.…”
Section: Methodsmentioning
confidence: 99%
“…Data were for the period 2000–2013 at the 100 m grid cell resolution. The observation data were presence‐only (PO; number of observations given in Table ); however, we established presence–absence (PA) data based on observation records from eight methodical recorders (see Mair et al., for details). We also established repeat‐visit detection/non‐detection data based on presence‐only records of 35 old‐forest indicator species of dead wood‐dependant fungi.…”
Section: Methodsmentioning
confidence: 99%
“…It will also be important to encourage integration and compatibility among taxonomically and/or geographically overlapping systems in order to encourage the formation of a "wildlife observation network" that provides scientists, managers, and the public with information about wildlife. These federated, standardized systems of wildlife observations will be instrumental in understanding and monitoring large-scale ecological characteristics and processes, such as extensive, taxonomically-focused monitoring (e.g., Gardiner et al, 2012), conservation success (Homayoun and Blair, 2016;Miller et al, 2017), changes in species distributions (Mair et al, 2016), mammalian invasions (Maistrello et al, 2016;Courchamp et al, 2017), and changes in species occurrence and abundance in response to climate change.…”
Section: Participatory Ecological Modelingmentioning
confidence: 99%
“…Involving society directly in scientific investigation can transform science from an exclusive process, remote from peoples' dayto-day experience, to one that includes millions of new environmental data collectors (Goodchild, 2007) and is participatory and has immediate relevance and value (Ceccaroni et al, 2016). Projects involving citizen/volunteer scientists have grown considerably in recent years (Silvertown, 2009;Conrad and Hilchey, 2010;Roy et al, 2012), providing data collection at large geographic scales (Devictor et al, 2010), that are often of high-quality (e.g., Ratnieks et al, 2016), have been found to be useful for species-distribution modeling (e.g., Mair et al, 2016), and help connect people to nature and conservation problems (Cooper et al, 2007;Devictor et al, 2010). Sub-national and national governments including transportation organizations (e.g., Harris et al, 2016), increasingly are recognizing the importance of volunteer-collected information (e.g., Bowser and Shanley, 2013 and the Federal Crowdsourcing and Citizen Science Toolkit, https://crowdsourcing-toolkit.sites.usa.gov/).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation